2015
DOI: 10.1093/ehjci/jev006
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial strain measurement with feature-tracking cardiovascular magnetic resonance: normal values

Abstract: changes within the RV that are associated with adverse surgical outcomes and poorer prognosis following mitral valve surgery. Future studies are needed to confirm whether LGE is a new imaging biomarker that can be used to risk stratify severe asymptomatic MR patients for surgery. Abstract 110 Table 1 Features of patients with and without gadolinium enhancement Late gadolinium enhancement Number of patients MR fraction (%) Systolic RV volume (ml/ m 2) RV ejection fraction (%) Peak VO 2 (ml/ kg/min) VE/ VCO 2 No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
147
11
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(202 citation statements)
references
References 34 publications
35
147
11
9
Order By: Relevance
“…Longitudinal strain at 3.0T was numerically higher for females, with a P value approaching statistical significance. These results are similar to what has been published in previous studies by Lawton et al16 using tagging, and Taylor et al17 using feature‐tracking. On the other hand, other authors, including Augustine et al,18 using feature‐tracking, Neizel et al19 using SENC, and Kuznetsova et al20 using echocardiography found that women had similar circumferential and longitudinal strain to men.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Longitudinal strain at 3.0T was numerically higher for females, with a P value approaching statistical significance. These results are similar to what has been published in previous studies by Lawton et al16 using tagging, and Taylor et al17 using feature‐tracking. On the other hand, other authors, including Augustine et al,18 using feature‐tracking, Neizel et al19 using SENC, and Kuznetsova et al20 using echocardiography found that women had similar circumferential and longitudinal strain to men.…”
Section: Discussionsupporting
confidence: 92%
“…On reviewing the literature, it seems that there is no clear consensus on the relationship between age and strain. Oxenham et al23 and Neizel et al19 (Supplementary Table 1) did not observe any association between age and strain when assessed using tagged MR. Taylor et al17 described a positive association between circumferential strain but not longitudinal strain with age in individuals over the age of 50 years. Kuznetsova et al20 using echocardiography in 236 healthy subjects found that strain was inversely associated with age, consistent with the results at 3.0T in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Reference values for LV circumferential, radial and longitudinal strain have been published recently. 30,31 Assessment of ventricular deformation at rest and with inotropic stimulation using dobutamine has provided clinically relevant data in health 18,20 and disease states. 23, 24 Schneeweis et al 23 demonstrated the ability to use circumferential short-axis strain to identify inducible ischemia during intermediate and high-dose dobutamine stimulation.…”
Section: Ventricular Performancementioning
confidence: 99%
“…Normal values have been published48 but have yet to be validated on a large scale and cut-offs for specific disease states are yet to be established. Strain imaging in general is hampered by high naturally occurring variation and high test-retest variability.…”
Section: Strain Imagingmentioning
confidence: 99%